Five Cases of Non-Hodgkin B-Cell Lymphoma of the Ovary - Taylan Senol; Emek Doger; Ilker Kahramanoglu; Ayfer Geduk; Emre Kole; Izzet Yucesoy; Eray Caliskan (Hindawi Limited, 2014)
The involvement of the ovary in lymphomatous process is rare. Such an involvement may occur in 2 ways, primary or secondary. We report 5 cases of ovarian non-Hodgkin's lymphoma, with 3 of which primarily arising in the ovaries. Ovarian lymphoma can mimic more frequently occurring tumors including advanced epithelial carcinoma and radical surgery may be performed instead of a biopsy. The immunophenotypic and clinicopathologic features exhibited in this small series are described to call attention to early diagnosis and treatment of ovarian lymphoma. All patients were diagnosed as having DLBCL after ovary biopsy. Different treatment modalities were used and prognosis of the patients was reported.